2017
DOI: 10.1177/0021998317704709
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of 3D printed BaTiO3/PVDF nanocomposites

Abstract: This paper presents a fabrication process to enhance homogeneous dispersion of BaTiO 3 nanoparticles in polyvinylidene fluoride matrix nanocomposites using fused deposition modeling (FDM) 3D printing technique. The nanocomposites integrate the functional property (piezoelectric, pyroelectric, and dielectric) of BaTiO 3 with the flexibility and lightweight of polyvinylidene fluoride. Traditionally, the simple yet effective way to fabricate the nanocomposites includes solventcasting, spin-coating, and hot-emboss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
88
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(88 citation statements)
references
References 31 publications
0
88
0
Order By: Relevance
“…[6,7] However, it has an intrinsic low direct piezoelectric coupling coefficient, which is a drawback with regard to the piezoelectric effect and sensor applications. [7][8][9] Therefore, graphitic carbon such as graphene oxide or multiwall carbon nanotubes (MWCNTs) has been utilized to enhance both electric and stress transfer to the ceramic particles and uniform dispersion. [10][11][12] In order to better enhance stress reinforcing, it is studied that a 3-trimethoxysilylpropyl methacrylate (TMSPM) linker molecular is covalently grafted on the BT particle surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,7] However, it has an intrinsic low direct piezoelectric coupling coefficient, which is a drawback with regard to the piezoelectric effect and sensor applications. [7][8][9] Therefore, graphitic carbon such as graphene oxide or multiwall carbon nanotubes (MWCNTs) has been utilized to enhance both electric and stress transfer to the ceramic particles and uniform dispersion. [10][11][12] In order to better enhance stress reinforcing, it is studied that a 3-trimethoxysilylpropyl methacrylate (TMSPM) linker molecular is covalently grafted on the BT particle surface.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, these methods entail complicated and time-consuming processes, quality issues, etc. [8] Recently, additive manufacturing technology has been introduced to printing piezoelectric three-dimensional (3D) structures. [7,8,13] It is reported that the fused deposition modeling (FDM) 3D printing process significantly improves homogeneous dispersion of BT nanoparticles in the PVDF matrix, enhancing piezoelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…These composite material filled in the syringe extruding with the help of pressure unit to deliver the 3D shape of the material (Fig 1).various types of needles are taken place based on the volume of the required output model which can have the free movement in all three dimensional directions. The extruder deliver the material layer by layer based on the given CAD model [23] .…”
Section: B Printing Methodsmentioning
confidence: 99%
“…Recently, many research efforts have been made to combine functional devices such as piezoelectric sensor and energy storage with additive manufacturing (AM) due to its great potential for use in commercial applications . Selective laser sintering and binder jetting techniques, which are using a laser beam to fuse materials selectively and coating ceramic powders onto the printing bed, respectively, have been studied for printing BaFe 12 O 19 , PZT, and BaTiO 3 bulk ceramic materials .…”
Section: Introductionmentioning
confidence: 99%